Two-Dimensional Time-Domain Antenna Arrays for Optimum Steerable Energy Pattern with Low Side Lobes - Alberto Reyna; Marco A. Panduro; Gerardo Romero; Juvenal Villanueva; Fernando F. Rivera; Aldo L. Méndez (International Journal of Antennas and Propagation)
This document presents the synthesis of different two-dimensional time-domain antenna arrays for steerable energy patterns with side lobe levels. The research is focused on the uniform and nonuniform distributions of true-time exciting delays and positions of antenna elements. The uniform square array, random array, uniform concentric ring array, and rotated nonuniform concentric ring array geometries are particularly studied. These geometries are synthesized by using the well-known sequential quadratic programming. The synthesis regards the optimal true-time exciting delays and optimal positions of pulsed antenna elements. The results show the capabilities of the different antenna arrays to steer the beam in their energy pattern in time domain and how their performance is in frequency domain after the synthesis in time domain.